SALICYLIC ACID EFFECTIVENESS AS RESISTANCE INDUCER OF RICE PLANT AGAINST SHEATH BLIGHT PATHOGEN - Suharti, Woro Sri; Nur Hibah, Feby Laelia; Wiyantono, Wiyantono (Agros Journal of Agriculture Science, 2023)
This study aims to determine the effectiveness of salicylic acid in inhibiting the growth of Rhizoctonia solani in vitro and to determine the effect of salicylic acid in increasing rice plants' resistance to rice sheath blight disease. In the in vitro research stage, the antifungal activity of salicylic acid was assayed with 5 levels of concentration. The observed variable was the percentage of R. solani mycelium growth inhibition. The next stage of research was carried out in planta. The observed variables in the resistance assay were the pathosystem, growth, morphological, and physiological components. Based on the observed variables of pathosystem components, salicylic acid can reduce the intensity of rice sheath blight both on an in vitro and in planta. Based on observations of morphological and physiological components, the salicylic acid was able to increase plant resistance by thickening of the leaf epidermis and increase the phenolic compounds.